(untitled) (REMUNOM, 2024)
Introduction: Chronic kidney disease (CKD) is a serious and progressive condition characterized by reduced glomerular filtration for a period of more than three months, leading to complications and limitations in quality of life. Therefore, it requires monitoring by a multidisciplinary team, highlighting nursing assistance in preventing injuries and illnesses, taking into account risk factors for this, such as diabetes mellitus and systemic arterial hypertension. Objective: to identify nursing actions to prevent chronic kidney diseases. Methodology: this is an integrative bibliographic review, in which data collection was based on the database available in the Virtual Health Library (VHL), Google Scholar and Scientific Electronic Library On line (SciELO) in the period from 2016 to 2024 Result: Nursing is fundamental, especially in education with these individuals with CKD, contributing to the promotion and prevention of diseases and providing improvements in quality of life through actions. Conclusion: CKD is a challenge and a public health problem that requires attention from health professionals as it is an asymptomatic disease, which requires nursing interventions depending on the problems, offering support through communication, guidance on lifestyle changes, practice of physical activity and nutrition favoring better quality.